The relationshop of physical recreation and leisure participation on family relationship quality and satisfaction - Villaflor, Amber Maria Ysabel M.
This mixed-methods study investigated the relationship between physical recreation and leisure participation and family relationship quality and satisfaction among selected Filipino families residing in Metro Manila. The study involved 53 individuals who live with their families, specifically 33 adult children and 20 parents. Three metrics were used to gather quantitative data — the Family Leisure Activity Profile (FLAP), the Brief Family Relationship Scale (BFRS), and the Satisfaction with Family Life Scale (SWFLS). For the qualitative data, semi- structured interviews were conducted with both adult children and their parents. Descriptive analysis and Spearman's Correlation were used to analyze the quantitative data, while thematic analysis was used for the qualitative data. Findings revealed that while both parents and adult children exhibit low participation in physical leisure activities, they exhibit moderate to high levels of satisfaction when they do engage. A significant positive relationship was found between core activity participation and family relationship quality among adult children; however, no significant correlation was observed between leisure participation and overall family satisfaction in either group. The study also found that physical leisure activities contribute to enhanced communication patterns, emotional bonding, and a sense of family cohesion, despite challenges such as conflicting interests, physical capabilities, and time constraints. The study recommends incorporating physical leisure into family development education, fostering inclusive planning within households, and pursuing future research across diverse family structures.